Soil Biodegradation of Unidirectional Polyhydroxybutyrate-Co-Valerate (PHBV) Biocomposites Toughened With Polybutylene-Adipate-Co-Terephthalate (PBAT) and Epoxidized Natural Rubber (ENR) - Zaidi, Zain; Mawad, Damia; Crosky, Alan (Frontiers in Materials, 2019)
The detrimental impact of discarded plastics on the environment has become of increasing concern and this has led to the development of environmentally friendly ‘green’ polymers. PHBV is one such green polymer that offers biodegradability and renewability, however its mechanical performance is quite limited. This can be improved by reinforcement with natural fibres to form green composites, which offer better mechanical properties while retaining biodegradability. There are, however, few studies examining the biodegradation of toughened PHBV composites. In this work, the biodegradation properties of PHBV/30 vol.% unidirectional flax composites both untoughened and toughened with PBAT and ENR, were studied. Composites were prepared by compression moulding PHBV powder interleaved with unidirectional flax fabric. The toughening agents were cryoground and mixed with the PHBV powder prior to moulding. Biodegradation was conducted in a natural outdoor soil environment and biodegradability was evaluated through weight loss analysis, optical microscopy and electron microscopy. The biodegradability of neat PHBV was minimal but was increased markedly by addition of flax fibres. The toughened composites showed a faster degradation rate than untoughened PHBV/flax, with PHBV/ENR/flax composites having the highest rate likely due to a specific strain of bacteria found worldwide in soil that attacks natural rubber. The biodegradation properties of the composites were superior to those of conventional plastics used in applications such as computer and mobile phone casings, which indicates potential suitability of this class of materials for these applications.